UJI TOKSISITAS EKSTRAK LEMPUYANG GAJAH (Zingiber zerumbet) TERHADAP LARVA UDANG (Artemia salina Leach.) - Sintha Suhirman; Hernani Hernani; Cheppy Syukur (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
Zingiber zerumbet has been used for long time as a traditional medicine to cure dysentri, stoma-chache, and also as carminative. The present work was to study the toxicity of extract of Z. zerumbet used Brine Shrimp Lethality Test (BSLT) method and A. salina as bio indicator. The raw material came from Bogor, Subang, Sumedang and Garut. The method of quality was used Materia Medika Indonesia (MMI) such ash content, ash insoluble in acid, water and alcohol soluble extractives and also fiber, starch and curcumin contents. Extracts were made by mace-ration combination with stirring and 3 types of solvents, such as polar (methanol), semi polar (ethyl acetate) and non polar (hexane). The chemical compounds were analyses by thin layer chromatography (TLC) with toluene : ethyl acetate : acetic acid = 8 : 2 : 2 drops as a eluen and 50% sulphuric acid as spray and GCMS. The result showed that there was variation between areas for ash, ash insoluble in acid, water and alcohol soluble extractives. And also in the fiber, starch and curcumin contents were different. The highest of water and, alcohol soluble extractives were from Garut followed by Sumedang. For fiber, starch and curcumin contents were from Sume-dang, Bogor and Subang, respectively. The highest and the lowest yield of extract were from ethyl acetate, Bogor (8.30%) and hexane, Garut (1.49%). The highest and the lowest LD5o of ex-tracts were from ethyl acetate, it was 1.85 ppm and 108.05 ppm, respectively. The result of TLC sho-wed that there were differences in chemical compound separations from extracts between areas, respectively. The identification of chemical compound was showed that the chemical com-ponent of extract which was showed the highest LD5o has the mixture of organic compound such as buthyl hexadecanoat, followed by octadeca-noate acid, hexacosan; and also the component which found in zingiberaceae family such as 3-hydroxy-ll-hyperoxy bisabolan-1,9-dien; 2', 4', 5' trimethoxyphenyl butadien, 7-(4'hyroxyi-3'metho-xyphenyl)-1 hept-4-en-3-on and 1,7 diphenyl-3,5 -heptan dion.